An evaluation of the completeness of safety reporting in reports of complementary and alternative medicine trials - Galipeau James; Wieland L Susan; Manheimer Eric; Tsertsvadze Alexander; Garritty Chantelle; Singh Kavita; Turner Lucy-Ann; Moher David (BMC, 2011)
Abstract Background Adequate reporting of safety in publications of randomized controlled trials (RCTs) is a pre-requisite for accurate and comprehensive profile evaluation of conventional as well as complementary and alternative medicine (CAM) treatments. Clear and concise information on the definition, frequency, and severity of adverse events (AEs) is necessary for assessing the benefit-harm ratio of any intervention. The objectives of this study are to assess the quality of safety reporting in CAM RCTs; to explore the influence of different trial characteristics on the quality of safety reporting. Methods Survey of safety reporting in RCTs published in 2009 across 15 widely used CAM interventions identified from the Cochrane Collaboration's CAM Field specialized register of trials. Primary outcome measures, the adequacy of reporting of AEs; was defined and categorized according to the CONSORT for harms extension; the percentage of words devoted to the reporting of safety in the entire report and in the results section. Results Two-hundred and five trials were included in the review. Of these, 15% (31/205) reported that no harms were observed during the trial period. Of the remaining 174 trials reporting any safety information, only 21% (36/174) had adequate safety reporting. For all trials, the median percentage of words devoted to the reporting of safety in the results section was 2.6. Moreover, 69% (n = 141) of all trials devoted a lesser or equal percentage of words to safety compared to author affiliations. Of the predictor variables used in regression analysis, multicenter trials had more words devoted to safety in the results section than single centre trials (P = 0.045). Conclusions An evaluation of safety reporting in the reports of CAM RCTs across 15 different CAM interventions demonstrated that the reporting of harms was largely inadequate. The quality of reporting safety information in primary reports of CAM randomized trials requires improvement.